Religious entanglements between Germans and Indians, 1800-1945 - Schwaderer, Isabella; Jonker, Gerdien (Palgrave series in Asian German studies, 2023)
1 Introduction -- 2 ‘To Read in an Indian Way’ (Johann Gottfried Herder): Pre-Emergent Colonial Epistemologies in Indian–German Entanglements, Showcased in Protestant Theology c.1800 -- 3 In Search of Purity: German-Speaking Vegetarians and the Lure of India (1833–1939) -- 4 The Indian Challenge: Indology and New Conceptions of Christianity as ‘Religion’ at the End of the Nineteenth Century -- 5 Death and Transfiguration: Religion and Belonging in Felix Gotthelf’s Indian Opera Mahadeva (1910) -- 6 The Indian Parsifal: Revisiting Felix Gotthelf’s Forgotten Opera Mahadeva -- 7 Modernism in Disguise? Neglected Aspects of the So-Called Revival of a Classical Indian Dance Form -- 8 ‘The Priestess of Hindu Dance’: Leila Sokhey’s Repertoire and Its Reception in the Netherlands and Germany (1927–38) -- 9 Roaming Between East and West: In Search of Religious Ecstasy in the Interwar Period -- 10 Negotiating Germanness with Indian Religious History: Transfers of Academic Knowledge and Notions of völkisch Belief -- 11 Hakenkreuz, Swastika and Crescent: The Religious Factor in Nazi Cultural Politics Regarding India -- 12 Curating the Fragments of Local Modernities: The Menaka Digital Archive from the Perspective of Ongoing Research.